2021
DOI: 10.48550/arxiv.2110.15254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isospin and momentum polarized orders in bilayer graphene

Abstract: Electron bands in Bernal-stacked (nontwisted) graphene bilayers in a transverse electric field feature field-tunable bandgaps and band dispersion that flattens out as the field increases. The effects of electron interactions are sharply enhanced in this regime, leading to a cascade of correlated phases exhibiting isospin (spin-valley) and momentum polarization orders. The momentum polarization, driven by exchange interactions, originates from a "flocking" effect, wherein all carriers condense into one, two or … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On top of this cascade of isospin orders, other symmetry-breaking orders are predicted theoretically, e.g. the momentum space polarization wherein all carriers are shifted into one, two or three pockets at the band minima produced by the trigonal warping effects [51,52].…”
mentioning
confidence: 98%
“…On top of this cascade of isospin orders, other symmetry-breaking orders are predicted theoretically, e.g. the momentum space polarization wherein all carriers are shifted into one, two or three pockets at the band minima produced by the trigonal warping effects [51,52].…”
mentioning
confidence: 98%
“…Note added: Recently, we found that Ref. [29] discusses momentum condensation ("flocking" effect) in Bernal bilayer graphene with three disjoint Fermi pockets whose microscopic origin is similar to the formation of nematic Fermi surface we discuss here in ABC trilayer graphene.…”
Section: At Low Carrier Densities |𝑛 𝑒 |mentioning
confidence: 91%